Analisis biaya pasien Severe Cutaneous Adverse Reactions (SCARs) - Qarriy 'Aina Urfiyya; Musa Fitri Fatkhiya; Dyah Aryani Perwitasari; Sri Awalia Febriana; Woro Supadmi (Universitas Islam Indonesia, 2022)
Background: Severe Cutaneous Adverse Reactions (SCARs), including Stevens-Johnson Syndrome (SJS), Toxic Epidermal Necrolysis (TEN), and Drug Reaction with Eosinophilia and Systemic Symptom (DRESS), were the idiosyncratic reactions most commonly caused by drugs which have an impact on increasing the patient's financial burden. Objectives: This study aims to determine the highest cost component and the illness cost in patients suffering from Severe Cutaneous Adverse Reactions (SCARs). Methods: This study was an analytic observational study with a cross-sectional design. We collected direct medical costs, direct non-medical costs, and indirect costs for inpatients with SJS, TEN, and DRESS at Dr. Sardjito Yogyakarta Hospital from 2014-2018, retrospectively. Based on the societal perspective, we defined the highest cost component and the illness cost in patients with SCARs. Results: The highest cost component for SJS, and TEN patients were obtained in the health professional services (24,1% and 25,2%, respectively). Meanwhile, the highest cost component for DRESS patients was the cost of drugs (20,2%). The total illness cost of 47 SCARs patients (22 SJS patients, 6 TEN patients, and 19 DRESS patients) was IDR 666.615.321, with the highest average cost for TEN patients, followed by SJS and DRESS (IDR 16.510.595, IDR 14.205.545, and IDR 13.445.555, respectively). Conclusions: The highest cost component was the health professional services in SJS and TEN patients and the cost of medicine for DRESS patients. The management of SCARs requires considerable cost, and it is still being a financial burden on the patients.